2020
DOI: 10.3390/ijerph17186846
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hippotherapy on the Body Posture in a Sitting Position among Children with Cerebral Palsy

Abstract: The purpose of this study was to assess the influence of hippotherapy (therapy with horses) on posture and body function among children with cerebral palsy. A case–control study included forty-five children aged 6–12 years, classified as Gross Motor Function Classification System (GMFCS) level I or II, with spastic diplegia or hemiplegia. The participants were randomly divided into three groups: study I (n = 15), study II (n = 15) and control (n = 15). The children from the study groups attended 30min hippothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 20 publications
1
35
0
3
Order By: Relevance
“…These studies revealed positive gains in each of these areas when hippotherapy was used as a treatment tool. 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 Over the past 20 years, additional research in hippotherapy has been published within occupational therapy and SLP. The number of peer-reviewed hippotherapy publications follows in the same order with the most publications from physical therapy, followed by occupational therapy, and finally SLP.…”
Section: History and Researchmentioning
confidence: 99%
“…These studies revealed positive gains in each of these areas when hippotherapy was used as a treatment tool. 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 Over the past 20 years, additional research in hippotherapy has been published within occupational therapy and SLP. The number of peer-reviewed hippotherapy publications follows in the same order with the most publications from physical therapy, followed by occupational therapy, and finally SLP.…”
Section: History and Researchmentioning
confidence: 99%
“…86,87 One CP study analyzed the effects of the exercise intervention according to demographic characteristics and found that younger children aged 6 and 7 had improved sitting scores with hippotherapy compared with no hippotherapy, whereas children aged 8 through 12 had similar scores, but there was no difference in the effect of the intervention based on disability level at baseline. 114 Limited evidence in participants with incomplete SCI, found having better function and more recent injury at baseline associated with better response to aerobic interventions than those with worse function and longer time since injury. 104,105,112…”
Section: Kq 3 Effects Of Patient Factors On the Benefits And Harms Of Physical Activitymentioning
confidence: 99%
“…Patients with cerebral palsy (CP) often have a permanent disorder of mobility, muscle tone, and posture development, which limits their function in daily activities [ 1 ]. CP is related to the abnormal signal transmission between the brain and the extremities [ 1 ], and causes various symptoms, including spasticity, contracture and uncoordinated movement, and this, then, affects movement abilities [ 2 ]. The symptoms of CP usually manifest as a variety of dyskinetic effects on the extremities of the body.…”
Section: Introductionmentioning
confidence: 99%